The Effectiveness of Cooper Method to Teach Reading Comprehension to the Seventh Grade Students of MTs Nurussalam Sidogede Belitang OKU Timur: Cooper method, teaching, and reading comprehension - ulfa, maria; Franzhardi, Didi; Yahya (English Education Program, Education Faculty, Universitas Nurul Huda, 2022)
The problem of this study is the effectiveness of cooper method to teach reading comprehension at the seventh grade students of MTs Nurussalam Sidogede Belitang OKU Timur. The objective of this study is to know whether or not the cooper method effective to teach reading comprehension. In this study, experimental method was used. The population was all of the seventh grade students. The total number of population was 70 students. The sample was 70 students taken through cluster random sampling, consisting of 35 students as the experimental group and 35 students as control group. The result of experimental group in the pre-test was 81.14. The highest score of the students was 90, the lowest score was 65, and while the median score was 80, and modus score was also 80. In the post-test control group, the mean score was 62.71. The highest score was 60, while the lowest was 55, and While the median score was 60, and modus score was 55. In fact, the students' scores in the post-test were better than those in the pre-test. The result of the matched t-test calculation was 10.77. It was higher than 1.697 (The critical value). It can be said that the alternative hypothesis (Ha) was accepted and the null: hypothesis (Ho) was rejected. It means that the teaching reading by using cooper method was effective at MTs Nurussalam Sidogede Belitang OKU Timur.